Fast assembly of fock matrices utilising symmetry properties of the basis set - Brailsford, David F.; Hylton, Jane (Elsevier, 1973)
A method of assembling the elements of the Fock matrix is described which is a modification of that due to Dacre. Lists of symmetry equivalent one-electron integrals are used as pointers to abbreviate the process of collecting two-electron integrals into the Fock matrix.